An abbreviated Philosophy of Geetiswami Gokulananda Sinha with Kalaguru Bishnuprasad Rabha - Probhat Kumar Sinha (Probhat Kumar Sinha, 2021)
This books presents the philosophy preached by Geetiswami Gokulananda Sinha with Kalaguru Bishnuprasad Rabha.
Keywords: Philosophy; Bishnupriya; English; Bishnupriya